Alteration of the Gut Microbiota and Its Effect on AMPK/NADPH Oxidase Signaling Pathway in 2K1C Rats. (22nd May 2019) - Yu, Hui; Qin, Lei; Hu, Hai; Wang, Zhanli
Abstract : Background . The purpose of this study was to evaluate the alteration of the gut microbiota and its effect on adenosine monophosphate-activated protein kinase (AMPK)/nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase) signaling pathway in two-kidney one-clip (2K1C) rats. Methods . The 2K1C rat models were established. The rats were randomly divided into the following 2 groups: 2K1C group and sham group. Alterations of the gut microbiota were analyzed based on the high throughput sequencing method. Plasma concentrations of short chain fatty acids (SCFAs) were measured by chromatography. The protein expression of phosphorylated AMPK and acetyl-CoA carboxylase (ACC) was determined by western blotting. NADPH oxidase activity was measured by a luminometer. Results . Microbial community analyses revealed that the structure and composition of the gut microbiota were significantly disrupted in 2K1C rats when compared to sham rats. This disruption was associated with the drastic increase in relative abundance of the genera Prevotella and the decrease in SCFA-producing bacterial population. We further confirm that SCFAs produced by the gut microbiota influence NADPH oxidase activity through AMPK. Conclusions . Our data implicated the important role of gut microbiota in the regulation of AMPK/NADPH oxidase signaling pathway.